III Seminario de Enfermería en Unidades de emergencia, urgencias y reanimación cardiopulmonar (RCP) - Llivi Ruilova, Danny Vicente (2023)
From July 5 to 8 of this year, the III NURSING SEMINAR IN EMERGENCY UNITS, EMERGENCIES AND CARDIOPULMONARY RESUSCITATION (CPR) was held, organized by the aforementioned career and with the endorsement of the UEB Public Company; the same one that had the presence of the Mgt. Silvana López Paredes, Dean; mgt. María Olalla, responsible for the race; faculty and students.